Pengembangan Perangkat Pembelajaran IPA Terpadu Model Nested Berbasis Perahu Phinisi untuk Meningkatkan Keterampilan Komunikasi dan Pengetahuan Konseptual - Andi Asmar*; I Gusti Putu Suryadarma (Universitas Syiah Kuala, 2021)
Conventional learning models that still dominate the science learning process have a negative impact on learning psychology and student learning outcomes, for example the lecture method. In addition, the integration of local knowledge in learning almost done because the teacher thought local knowledge of science content is not relevant to modern science. This study has the prospect to develop an integrated learning tools nested models based on local wisdom phinisi boat. Products developed focuses on improving communication skills and conceptual knowledge of students. Adapting product development methods development framework Dick and Carey to modify it in 5 stages. Stages of needs analysis, product design, product development, product implementation and evaluation, and the final product. The results of product development tested in a limited class of the class VII SMPN 32 Bulukumba the 15 students who have been selected by purposive sampling. The choice of subjects represented each of 5 students with low, medium, and high abilities. Primary data were obtained from the assessment of the product by 2 experts and through the assessment questionnaire. The feasibility of the product in the category